2013
DOI: 10.1016/j.ijppaw.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Using occupancy models to investigate the prevalence of ectoparasitic vectors on hosts: An example with fleas on prairie dogs

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…If an epizootic does not erupt in a dry year, and if precipitation returns, fleas might already be abundant because of the preceding drought, and the returning precipitation and accompanying mild temperatures might propel an epizootic vortex (Ray and Collinge ). Increased primary production facilitates reproductive output for prairie dogs (Knowles , Facka et al , Eads ), which might provide context for behavioral interactions among prairie dogs due to proximity, allowing for exchanges of fleas among hosts (Tripp et al , Eads et al ). Mild temperatures in wet years might favor plague transmission by fleas (Williams et al ), for example, while they attempt to feed on blood from hosts above ground.…”
Section: Discussionmentioning
confidence: 99%
“…If an epizootic does not erupt in a dry year, and if precipitation returns, fleas might already be abundant because of the preceding drought, and the returning precipitation and accompanying mild temperatures might propel an epizootic vortex (Ray and Collinge ). Increased primary production facilitates reproductive output for prairie dogs (Knowles , Facka et al , Eads ), which might provide context for behavioral interactions among prairie dogs due to proximity, allowing for exchanges of fleas among hosts (Tripp et al , Eads et al ). Mild temperatures in wet years might favor plague transmission by fleas (Williams et al ), for example, while they attempt to feed on blood from hosts above ground.…”
Section: Discussionmentioning
confidence: 99%
“…We note that while multi-model inference has been used in a few studies similar to ours [32][34], the formal treatment of detection failures has hardly entered the vector ecology literature thus far [14], [28], [29], [35], [36]. Yet, as discussed below, standard approaches can yield biased effect-size estimates and SEs; site-occupancy models may provide a more reliable and realistic picture of key population parameters and their environmental correlates [15], [16].…”
Section: Discussionmentioning
confidence: 99%
“…, Eads et al. , ). Some studies have suggested that high precipitation enhances growth in populations of fleas (Stapp et al.…”
Section: Introductionmentioning
confidence: 99%